Brand positioning and consumer taste information - Arcan Nalca; Tamer Boyaci; Saibal Ray (European School of Management and Technology (ESMT), 2017)
In this paper, we study how a retailer can benefit from acquiring consumer taste information in the presence of competition between the retailers store brand (SB) and a manufacturers national brand (NB). In our model, there is ex-ante uncertainty about consumer preferences for distinct product features, and the retailer has an advantage in resolving this uncertainty because of his close proximity to consumers. Our focus is on the impact of the retailers information acquisition and disclosure strategy on the positioning of the brands. Our analysis reveals that acquiring taste information allows the retailer to make better SB positioning decisions. Information disclosure, however, enables the manufacturer to make better NB positioning decisions - which in return may benefit or hurt the retailer. For instance, if a particular product feature is quite popular, then it is beneficial for the retailer to incorporate that feature into the SB, and inform the manufacturer so that the NB also includes this feature. Information sharing, in these circumstances, benefits both the retailer and the manufacturer, even though it increases the intensity of competition between the brands. But, there are situations in which the retailer refrains from information sharing so that a potentially poor positioning decision by the NB makes the SB the only provider of the popular feature. The retailer always benefits from acquiring information. However, it is beneficial to the manufacturer only if the retailer does not introduce an SB due to the associated high fixed cost.
urn:nbn:de:101:1-2017121122222
Keywords: 650; supply chain management; uncertain consumer taste; product introduction; product positioning; store brands; national brands; information acquisition; information sharing; vertical differentiation; horizontal differentiation